Mixed competition and technology licensing in a supply chain - Zhang, Huaige; Zhang, Yu; Zhou, Menghuan (Frontiers in Psychology, 2022)
Technology licensing as a vital part of business behavior in many industries has drawn a fair amount of attention in industrial organization literature. Most existing literature on licensing decision assumes that all firms engage in Cournot or Bertrand competition, while the type of mixed competition may affect the choice of licensor. Then what decision will licensor make in the case of different mixed competitions? This paper studies the optimal technology licensing contract of a licensor firm engaging in different mixed competitions (Cournot-Bertrand or Bertrand-Cournot) with a potential licensee in a differentiated duopoly market considering one upstream firm (supplier) that provides key inputs. We find that if either the royalty or fixed-fee licensing is applied, the licensor favors royalty licensing under Bertrand-Cournot competition when the degree of substitution is small, and prefers fixed-fee licensing no matter under what kind of mixed competition as the degree of substitution increases. For the case of fixed-fee licensing, the result shows that profits of licensor are the same under different types of mixed competition. Besides, fixed-fee licensing is not always the optimal choice for consumers and they would prefer royalty licensing when the degree of substitution is very small.